Cardio classics revisited: Focus on the role of amlodipine - Owen, A.; Reid, Christopher (2012)
Amlodipine is a long-acting, dihydropyridine calcium antagonist now widely used for lowering of elevated blood pressure. In recent years it has been shown to be effective in reducing both blood pressure and risk of cardiovascular (CV) events when used in combination with other antihypertensive agents of different classes. Strong evidence of cardiovascular benefit has been attained for combination of amlodipine with diuretics or angiotensin converting enzyme (ACE) inhibitors in a number of high-risk CV groups, including those with established coronary artery disease, diabetes, and at risk of renal disease. Combination therapies of amlodipine with other agents eliciting renin-angiotensin-aldosterone system blockade (angiotensin II receptor blockers or renin inhibitors) have been shown to be effective blood pressure-lowering strategies, but await the results of ongoing trials for direct evidence of benefit for renal disease progression and CV morbidity and mortality.